Is there a link between physical activity and Amyotrophic Lateral Sclerosis? (Epidemiology, Biostatistics, and Public Health, 2022)
The Amyotrophic Lateral Sclerosis (ALS) is a chronic and progressive neuro-degenerative pathology that starts in adult age and usually leads patients to death for respiratory distress after 3 years from the onset of symptoms In some studies, vigorous and continuous physical activity due to heavy working activity and sport is associated with ALS. On the other hand other studies are against this association. A study carried out in Europe found overall physical activity is associated with reduced odds of having ALS (OR=0.65, 95% CI=0.48-0.89), and the same protective factor is seen for work-related physical activity (OR=0.56, 95% CI=0.36-0.87) and organized sports (OR=0.49, 95% CI=0.32-0.75.A recent literature review found that football/soccer may be considered as a possible risk factor for ALS (level C) and there is a strong need for further research that must take into account the numerous confounding factors that could be present in this field. However only well conducted observational studies, such as cohort and case-control studies, carried out with the same design in different countries could give a final answer to this suspected but still unconfirmed association